The ethanol extract of Involcucrum castaneae ameliorated ovalbumin-induced airway inflammation and smooth muscle thickening in guinea pigs. (10th February 2019) - Ye, Yujie; Mo, Shuyuan; Feng, Wenya; Ye, Xiaochun; Shu, Xiang; Long, Yuxi; Guan, Yeli; Huang, Jiangeng; Wang, Jianping
Abstract: Ethnopharmacological relevance: Involucrum castaneae (IC)is used in Chinese folk medicine to treat various lung diseases, as well as for its reducing phlegm and anti-inflammatory properties. Aim of the study: The purpose of this experiment is to verify the effect of IC on airway inflammation, responsiveness in ovalbumin (OVA)-induced asthmatic guinea pigs. The main chemical components of IC were also analyzed. Materials and methods: The potential of the ethanol extract of Involucrum castaneae (EEIC) to protect against OVA-induced allergic airway response in guinea pigs was investigated. The latency of asthma in guinea pigs were recorded after the allergic asthma induced. Enzyme-linked immunosorbent assay (ELISA) was used to measure the levels of immunoglobulin E (IgE), interleukin-5 (IL-5), nerve growth factor (NGF) and interferon-γ (IFN-γ) in asthma allergy. Reverse transcription-PCR (RT-PCR) was used to detect the expression of IL-5 mRNA in asthmatic guinea pig lungs. Paraffin sections of lung tissue were used to analyze pathological changes. The total flavonoid content was determined and the chemical components were analyzed by LC-MS/MS. Results: It was found that EEIC was able to reduce the number of eosinophil (EOS) in bronchoalveolar lavage fluid (BALF) and peripheral blood (PB) in the guinea pig model of OVA -induced asthma. Meanwhile, it also significantly reduced the levels of inflammation-related factors IgE and IL-5, decreased the expression of IL-5 mRNA in lung tissue, and increased the level of IFN-γ. Pathological examination of paraffin section of lung tissue showed that EEIC can reduce the thickening of bronchial smooth muscle and reduce the infiltration damage of tissues by various inflammatory cells. The presence of flavonoids, terpenoids and phenolic compounds in EEIC might be responsible for these activities. Conclusion: IC alleviated airway inflammation and smooth muscle thickening in guinea pigs with OVA-sensitized allergic asthma. The paper explains the traditional efficacy and material basis of IC and lays a foundation for further development. Graphical abstract: